THU0291 Not Only Organ Involvement, but Also Inflammation Level Is Heterogeneous in IGG4-Related Disease. (9th June 2015) - Karadag, O.; Kalyoncu, U.; Ayhan, A.S.; Donmez, I.; Kilic, L.; Akdogan, A.; Akdogan, B.; Hazirolan, T.; Baydar, D.E.; Ertenli, I.; Kiraz, S.
Abstract : Background: IgG4-Related Disease (IgG4-RD) is a recently recognized condition with a wide range of organ involvements.Few data exist on the global perspective of IgG4-RD regarding prevalence and the frequencies of the different clinical presentations. Objectives: This study is aimed to describe the clinical and laboratory characteristics of a series of patients diagnosed with IgG4-RD in Turkey. Methods: A retrospective study was performed. Demographic, clinical characteristics and imaging studies including PET-CT, in addition to serum IgG4 levels were recorded. Totally 48 pathologic specimens of the patients were re-evaluated regarding IgG4-RD morphologic findings and IgG4/total Ig G ratio. Patients were diagnosed according to diagnostic criteria for IgG4-RD. 1 Results: Totally 27 patients fulfilling the diagnostic criteria were included in the study, 18 of whom (66.7%) were male. Mean age at diagnosis was 55.9±11.8 years. Retroperitoneal fibrosis is the most common finding. Fourteen (51.8%) of the patients had more than one clinical involvement. Thirty percent of patients had lymphadenopathy. Nine (33.3%) of patients had any additional cardiovascular involvement (thoracic aortitis/inflammatory abdominal aneurisms/coronary periarteritis). The global distribution by specific organ involvement was shown in Table. Three of the patients had normal serum IgG4 levels. Six patients had PET-CT. Patients had a wide range of inflammation assessed by PET-CT (SUV max levels were between 2.2-11.4). Twenty of the patients were pathologically proven IgG4-RD -16 of them had morphologic features and all had a ratio of IgG4/IgG ≥40%. Conclusions: The most usual presentation of IgG4 related disease in our study is middle aged males and as retroperitoneal fibrosis. Cardiovascular involvement, lymphadenopathy, and orbital/periorbital involvements were the other frequent findings. Not also the organ involvement but also inflammation level could be in a very wide range in IgG4-RD. More collaborative studies are required in order to assess the real prevalence of the disease and the frequencies of the different presentations. References: Guma M, Firestein GS. IgG4 relateddiseases. Best PractClinRheum 2012;26:425-438. Disclosure of Interest: None declared